The emergence of scalar meanings - Etxeberria, Urtzi; Irurtzun, Aritz (Frontiers in Psychology, 2015)
This paper analyzes the emergence of scalar additive meanings. We show that in Basque the same particle ere can obtain both the ‘simple additive’ reading (akin to English too) and the ‘scalar additive’ reading (akin to English even) but we argue that we do not have to distinguish two types of ere. We provide evidence, by means of a production and a perception experiment, that the reading is disambiguated by means of prosody (the placement of nuclear stress), which is a correlate of focus. We argue that the scalarity effect is generated by the combination of two presuppositions (a focus-induced one and a lexical one) and the assertion of the sentence.